Congenital communicating bronchopulmonary foregut malformation including ectopic pancreatic tissue in an infant - Noboru Oyachi; Fuminori Numano; Keiichi Koizumi; Tamao Shinohara; Hirochika Matsubara (Surgical Case Reports)
Abstract Background Several reports have documented that the pulmonary sequestration is in communication with the gastrointestinal tract and the concept of bronchopulmonary foregut malformation (BPFM) has become more widespread. However, there are few reports of the sequestration associated with the pancreas derived from the foregut. We describe the history and pathophysiology of BPFM including pancreatic tissue in a male infant with respiratory distress. Case presentation A male patient was born at 38 weeks of gestation and weighed 2752 g at birth. He developed pneumonia and was hospitalized at 3 months of age. Chest radiographs and CT scans led to the diagnosis of a lung abscess in the left lower intralobar pulmonary sequestration with aberrant arteries from the abdominal cavity. At 4 months of age, when the abscess had resolved, left lower lobectomy and the resection of the intralobar sequestration were performed. The pulmonary sequestration was conjoined with the esophagus. A fistula was found between the lower esophageal wall and the pulmonary sequestration. An additional small segment of the esophageal wall was excised. Histologically, the mediastinal surface of the sequestration tissue contained pancreatic tissue. Furthermore, esophageal and gastric tissue, cartilage tissue, and ciliated epithelium were confirmed. A definitive diagnosis of BPFM was made. Conclusions We postulated the rare case of a communicating BPFM with intrapulmonary sequestration on one end and the esophagus on the other forming a mass lesion, which included ectopic pancreatic tissue in a male infant.